Can Artificial Intelligence Treat My Urinary Tract Infections?—Evaluation of Health Information Provided by OpenAI™ ChatGPT on Urinary Tract Infections - Kevin Yinkit Zhuo; Paul Kim; James Kovacic; Venu Chalasani; Krishan Rasiah; Stuart Menogue; Amanda Chung (Société Internationale d’Urologie Journal)
Urinary tract infections (UTIs) are highly prevalent and have significant implications for patients. As internet-based health information becomes more relied upon, ChatGPT has emerged as a potential source of healthcare advice. In this study, ChatGPT-3.5 was subjected to 16 patient-like UTI queries, with its responses evaluated by a panel of urologists. ChatGPT can address general UTI questions and exhibits some reasoning capacity in specific contexts. Nevertheless, it lacks source verification, occasionally overlooks vital information, and struggles with contextual clinical advice. ChatGPT holds promise as a supplementary tool in the urologist’s toolkit, demanding further refinement and validation for optimal integration.